2020
DOI: 10.1063/5.0013430
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of ethanol permeation through single and double-lipid bilayers

Abstract: Permeation of small molecules through membranes is a fundamental biological process, and molecular dynamics simulations have proven to be a promising tool for studying the permeability of membranes by providing a precise characterization of the free energy and diffusivity. In this study, permeation of ethanol through three different membranes of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylserine (POPS), POphosphatidylethanolamine (POPE), and PO-phosphatidylcholine (POPC) is studied. Permeabilities are calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…Also, for higher concentrations, the ISD model does not capture the collective behavior of the permeating solute and its effects on the membrane. However, for compounds at low concentrations the estimates of the permeability coefficients from the ISD model are comparable to the unbiased estimates from transition-based counting 72 . Further studies on the permeability of small solutes through lipid membranes and the ISD in various scenarios are provided in the references 16 , 71 74 .…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Also, for higher concentrations, the ISD model does not capture the collective behavior of the permeating solute and its effects on the membrane. However, for compounds at low concentrations the estimates of the permeability coefficients from the ISD model are comparable to the unbiased estimates from transition-based counting 72 . Further studies on the permeability of small solutes through lipid membranes and the ISD in various scenarios are provided in the references 16 , 71 74 .…”
Section: Methodsmentioning
confidence: 73%
“…The permeation dynamics is assumed to be diffusive in the ISD model. Deviations from such an assumption may lead to inaccurate estimates of the permeability coefficients for permeants that interact strongly with one another or with the membrane 71 , 72 . Also, for higher concentrations, the ISD model does not capture the collective behavior of the permeating solute and its effects on the membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Also, for higher concentrations, the ISD model does not capture the collective behavior of the permeating solute and its effects on the membrane. However, for compounds at low concentrations the estimates of the permeability coefficients from the ISD model are comparable to the unbiased estimates from transition-based counting 68 . Further studies on the permeability of small solutes through lipid membranes and the ISD in various scenarios are provided in the references 16,[67][68][69][70] .…”
Section: Inhomogeneous Solubility-diffusion Modelmentioning
confidence: 73%
“…The permeation dynamics is assumed to be diffusive in the ISD model. Deviations from such an assumption may lead to inaccurate estimates of the permeability coefficients for permeants that interact strongly with one another or with the membrane 67,68 . Also, for higher concentrations, the ISD model does not capture the collective behavior of the permeating solute and its effects on the membrane.…”
Section: Inhomogeneous Solubility-diffusion Modelmentioning
confidence: 99%
“… 36 , 44 47 For POPC specifically, it has been shown that ethanol has high permeability and aggregates at the hydrophilic/phobic interface. 44 , 45 Shobhna and Kashyap 47 show that at significantly higher ethanol-to-lipid ratio vesicles still retain structures. When analyzing snapshots of solvent permeability ( Figures S3–S5 ), we observe evidence consistent with these trends of thinning, pore formation, and high permeability across POPC bilayers, as well as ethanol aggregation at the hydrophilic/phobic interface.…”
Section: Resultsmentioning
confidence: 99%